Situation Report: Czechoslovakia, 27 June 1984 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. The CMEA Summit Meeting: A First Assessment Prague Ideologist Calls for a World Communist Conference Czechoslovakia in Search of Oil from Iran Energy Shortages Ahead An Atmosphere of Criticism The Story of Two Priests: A Czech and a Slovak What Happened in Bratislava, or the Short Step from Prank to Politics